Novel N-1 substituted fluoroquinolones inhibit human topoisomerase I activity and exhibit anti-proliferative activity - Oppegard, Lisa M.; Delgado, Justine L.; Kulkarni, Chaitanya A.; Towle, Tyrell R.; Hart, Delaney E.; Williams, Bridget P.; Lentz, Sarah R. C.; Norris, Beverly J.; Flory, Craig M.; Schumacher, Robert J.; Murry, Daryl J.; Kerns, Robert J.; et al. (Investigational new drugs, 2019)
Summary Fluoroquinolone-class agents selectively target the bacterial type IIA topoisomerases DNA gyrase and topoisomerase IV, with a few exceptions that target eukaryotic type IIA topoisomerases. Fluoroquinolones bind and stabilize type IIA topoisomerase-DNA covalent complexes that contain a double-strand break. This unique mode of action is referred to as ‘topoisomerase poisoning’. We discovered that two novel fluoroquinolones having aryl functionality at the N -1 position, UITT-3-217 (217) and UITT-3-227 (227), could inhibit the catalytic activity of human topoisomerase II without stabilizing topoisomerase-DNA complexes, i.e., without poisoning it. Surprisingly, these compounds are more effective in inhibiting the catalytic activities of human and bacterial topoisomerase I. The National Cancer Institute’s 60 human tumor cell lines screen revealed significant anti-proliferative activities with 217 and 227 against the majority of 60 cancer cell lines. A proof of concept in vivo efficacy study using an HT-29 xenograft model of human colorectal cancer showed that 217 could inhibit the proliferation of human colorectal cancer cells to a degree comparable to fluorouracil in mice. Although 227 also exhibited anti-proliferative activity, it was not as effective as 217 in this xenograft model. These novel fluoroquinolones may serve as promising lead compounds for the development of new anticancer drugs.